PELUANG MANAJEMEN LABA PASCA KONVERGENSI IFRS: SEBUAH TINJAUAN TEORITIS DAN EMPIRIS - Cahyati, Ari Dewi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2011)
The convergency accounting standards to IFRS raises a variety of influences, in accordancewith IFRS characteristics such as : principle-based, the use of fair value and more disclosure. Principles-based standards require more judgment in its application, while the use of fair value items make the financial statements are presented with the actual values, more disclosure would reduce the level of information asymmetry. Convergence of IFRS is expected increasing financial reporting quality, such as, increased comparability and transparency of financial statements. Thus, with the convergence to IFRS expected reduce earnings management opportunities.